2022
DOI: 10.1021/acs.jafc.2c05743
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Quality Changes of Asparagus during Growth by Widely Targeted Metabolomics Analysis

Abstract: Asparagus is a popular vegetable and traditional medicine consumed worldwide due to its health benefits. The quality of asparagus, mainly attributed to small components like flavonoids and steroid, is quite differential as a result of different environments and maturities. However, the accumulation pattern and regulatory mechanism of metabolites in asparagus remain unclear so far. Herein, widely targeted metabolomics analysis was employed to study the quality and chemical composition variances of four asparagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The correlation coefficient between rutin and protodioscin was 0.345, which was consistent with the previous research results that genetic factors and light conditions affected the content of rutin and protodioscin in asparagus (Lee et al, 2010;Liu et al, 2022;Yi et al, 2019). The correlation between the mineral selenium and the other six indicators was also low (r < .5).…”
Section: Correlation Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…The correlation coefficient between rutin and protodioscin was 0.345, which was consistent with the previous research results that genetic factors and light conditions affected the content of rutin and protodioscin in asparagus (Lee et al, 2010;Liu et al, 2022;Yi et al, 2019). The correlation between the mineral selenium and the other six indicators was also low (r < .5).…”
Section: Correlation Analysissupporting
confidence: 90%
“…There was a significant positive correlation among total phenols, flavonoids, and rutin, especially between flavonoids and rutin (r = .93, p < .01), as rutin comprises the largest proportion (55%-98%) of flavonoids in asparagus (Liu et al, 2022;Yi et al, 2019).…”
Section: Correlation Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Based on our previous study and the MS/MS data reported in the literature, 4,10–28 a total of 342 metabolites were tentatively identified, which were divided into 11 categories, including 53 saponins, 47 flavonoids, 133 lipids, 33 phenolic acids, 31 amino acids, peptides and derivatives, 10 carbohydrates, 7 nucleosides, 9 organic acids, 4 alkaloids, 3 lignans and norlignans and 12 other compounds. The base peak intensity (BPI) chromatograms of the inedible parts of white and green asparagus are shown in ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analytical protocol included the gaining of lipids from asparagus lyophilizates by accelerated solvent extraction (ASE), the transfer of FAs and FuFAs into the corresponding methyl esters (FAMEs and FuFA‐MEs) and finally, their determination by gas chromatography with mass spectrometry operated in the selected ion monitoring mode (GC/MS‐SIM). Also, asparagus had been previously studied by non‐targeted metabolomic studies (Jiménez‐Sánchez et al, 2016; Liu et al, 2022), without indicating the presence of FuFAs. Hence, we additionally measured five white asparagus ASE extracts on FuFA‐containing TAGs by using LC‐Q‐Orbitrap‐high resolution mass spectrometry (HRMS) (Wiedmaier‐Czerny & Vetter, 2023).…”
Section: Introductionmentioning
confidence: 99%